Design and implementation of a centralized approach for multi-node localization - Hasan, Ola A.; T. Rashid, Abdulmuttalib; S. Ali, Ramzy; Qasim, Hamza H.; A. Al Sibahee, Mustafa; Audah, Lukman (International Journal of Electrical and Computer Engineering (IJECE), 2022)
In this paper, a centralized approach for multi nodes localization is introduced. This approach is based on using a beacon fixed at the lower middle edge of the environment. This beacon is provided with a distance sensor and can scan the environment to measure the distance between the detecting node and the beacon. Also, remote control is fixed on the beacon to distinguish the identity of the detecting node. Two nodes are used in this approach, each node contains eight cells, and each cell has a 5 mm IR transmitter and TSOP4P38 IR receiver. If any one of the IR receivers has received the beacon ID, the transmitter which belongs to the same cell will respond by sending the node ID to the beacon. The beacon measurements and the information received from the detected nodes are then used to estimate the location and orientation of the visible nodes and the results will be saved in the main computer. Several experimental results have been tested with different distances from the nodes to the beacon. Also, different rotation angles at the beacon have been experienced to analyze the performance of the introduced approach.